Transforming Growth Factor-β Signaling Regulates Tooth Root Dentinogenesis by Cooperation With Wnt Signaling - Zhang, Ran; Lin, Jingting; Liu, Yang; Yang, Shurong; He, Qi; Zhu, Liang; Yang, Xiao; Yang, Guan (Frontiers in Cell and Developmental Biology, 2021)
Proper differentiation of odontoblasts is crucial for the development of tooth roots. Previous studies have reported the osteogenic/odontogenic potential of pre-odontoblasts during root odontoblast differentiation. However, the underlying molecular pathway that orchestrates these processes remains largely unclear. In this study, ablation of transforming growth factor-β receptor type 2 (Tgfbr2) in root pre-odontoblasts resulted in abnormal formation of root osteodentin, which was associated with ectopic osteogenic differentiation of root odontoblasts. Disrupting TGF-β signaling caused upregulation of Wnt signaling characterized by increased Wnt6, Wnt10a, Tcf-1, and Axin2 expression. Interestingly, inhibiting Wnt signaling by deleting Wntless (wls) in Osteocalcin (Ocn)-Cre; Tgfbr2fl/fl; Wlsfl/fl mice or overexpressing the Wnt antagonist Dkk1 in Ocn-Cre; Tgfbr2fl/fl; ROSA26Dkk1 mice decreased ectopic osteogenic differentiation and arrested odontoblast differentiation. Our results suggest that TGF-β signaling acts with Wnt signaling to regulate root odontogenic differentiation.